C, O‐Chelated organotin(IV) derivatives as potential anticancer agents: Synthesis, characterization, and cytotoxic activity. (3rd January 2022) - Someșan, Adrian‐Alexandru; Vieriu, Sabina‐Mădălina; Crăciun, Alexandru; Silvestru, Cristian; Chiroi, Paul; Nutu, Andreea; Jurj, Ancuta; Lajos, Raduly; Berindan‐Neagoe, Ioana; Varga, Richard A.
Abstract: Organotin(IV) chemistry is nowadays in a continuous expansion due to the biological and medicinal potential found for some of these species. Within this study, the cytotoxic activity of several organotin(IV) compounds was investigated on two lung cancer cell lines (H522 and SK‐MES‐1) and on a normal lung cell line in order to have an overview of the toxicity and the selectivity of these derivatives. Moreover, the synthetic protocols, as well as the structural particularities of the novel organotin(IV) species, are also discussed. Hydrolysis of [2‐{(CH2 O)2 CR}C6 H4 ]2 SnPh2 [R = H (1 ), Me (2 )] with p ‐toluenesulfonic acid as a proton source afford the expected derivatives [2‐(O═CR)C6 H4 ]2 SnPh2 [R = H (3 ), Me (4 )]. When hydrochloric acid is used in these reactions, a chlorine‐phenyl exchange took place in addition to the removal of the acetal fragments and the following products [2‐(O═CR)C6 H4 ]2 SnPhCl [R = H (5 ), Me (6 )] were isolated. Treatment of 5 with 2 equiv of 3‐aminomethylpyridine in neat affords the imino(aryl)tin compound 2‐(3′‐PyCH2 N═CH)C6 H4 ]2 SnPhCl (7 ). The reaction between 6 and potassium nicotinate allows the isolation of the organotin(IV) carboxylate [2‐{O═C (CH3 )}C6 H4 ]2 SnPh[O(O)CC5 H4 N‐3] (8 ). Compounds 1 –8 were characterized by multinuclear NMR spectroscopy in solution, mass spectrometry, and IR spectroscopy, and their molecular structures were confirmed by X‐ray diffraction analysis. Compounds 1 –8 were investigated for their antitumoral effects on Homo sapiens lung cancer cell lines (H522 and SK‐MES‐1) and on a normal bronchial epithelial cell line, BEAS‐2B. Abstract : Syntheses of seven novel aryltin(IV) compounds bearing C, O ‐chelating ligands are reported. A new organotin(IV) imine was obtained following a simple synthetic protocol with easy workup. The MTT assays for eight compounds performed on both normal and lung cancer cell lines showed a statistical response at 10 nM, a lower dose than other treatments such as cisplatin.